The lifespan-extending MEK1 inhibitor trametinib promotes regulation of de novo lipogenesis enzymes by chaperone-mediated autophagy - Chen, Jiexian; Berg, Joshua; Burns, Calvin M.; Jia, Hanyi; Li, Xinna; Miller, Richard A.; Endicott, S. Joseph; Garcia, Gonzalo (Frontiers in Aging, 2025)
The availability of multiple slow-aging mice allows a search for possible shared mechanisms that affect the rate of aging. Previous work has shown downregulation of the MEK1-ERK-MNK kinase cascade, which regulates protein translation through eIF4E, in response to four anti-aging drugs. Here we show that decreased protein abundance of enzymes involved in hepatic de novo lipogenesis (DNL) is characteristic of mice exposed to two anti-aging drugs that modulate glucose homeostasis (acarbose and canagliflozin), as well as in calorically restricted mice and in two long-lived mutant models. The same pattern of changes in the de novo lipogenesis enzymes can be produced, in cultured cells or in intact mice, by trametinib, a drug that inhibits the MEK-ERK kinase cascade, and which has been shown to extend mouse lifespan. The trametinib effect on DNL enzymes is, unexpectedly, not related to transcriptional changes, but depends on selective protein degradation through chaperone-mediated autophagy. Our data support models in which chaperone-mediated proteomic alterations, triggered through the MEK1-ERK-MNK kinase pathway, may collaborate with mTORC1 changes to slow aging and extend mouse lifespan.